The TRIPS Agreement Article 73 Security Exceptions and the COVID-19 pandemic - Frederick M. Abbott (South Centre, 2020)
The COVID-19 pandemic has caused Governments to contemplate measures to override patents and other intellectual property rights (IPRs) in order to facilitate production and distribution of vaccines, treatments, diagnostics and medical devices. This paper discusses whether the COVID-19 pandemic may be considered an “emergency in international relations” and how WTO Member States may invoke Article 73 (“Security Exceptions”) of the TRIPS Agreement as the legal basis for overriding IPRs otherwise required to be made available or enforced. It concludes that the pandemic constitutes an emergency in international relations within the meaning of Article 73(b)(iii) and that this provision allows Governments to take actions necessary to protect their essential security interests.
Keywords: 300; Access to Medicines; Affordable Medicines; Article 73 TRIPS; Coronavirus; COVID-19; Diagnostics; Doha Declaration on the TRIPS Agreement and Public Health; Flexibilities; Global Health; Health; Intellectual Property; Intellectual Property Rights (IPRs); Investment Agreement; Medical Devices; Pandemic; Patent; Public Health; Security Exceptions; Trade; TRIPS; Vaccines; WHO; World Health Organization (WHO); World Trade Organization (WTO); WTO